KOMPARASI KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 X KOTO KABUPATEN TANAH DATAR - Rahmiyyatul Husna; Nursaid Nursaid (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this research was to describe the following things. First, to describe the writing skills of observation report texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. Second, to describe the writing skills of expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. Third, to analyze the comparison between the writing skills of observation report texts and expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. This research is a quantitative research with descriptive analysis. Based on the research findings, the following three things were concluded. First, the writing skills of observation report texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency, were in a good qualification (76.43). Second, the writing skills of expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency, were in more than sufficient qualification (74.07). Third, there was a significant difference between the writing skills of observation report texts and expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. Based on the hypothesis test conducted, it can be concluded that H1 is accepted because the tvalue is greater than the ttable. Therefore, there is a significant difference between the two texts.